Terapi Kelompok Pendukung untuk Meningkatkan Resiliensi pada Ibu yang Memiliki Anak Talasemia - Yudi Kurniawan; Fuad Nashori; Indahria Sulistyarini (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aims to increase resilience in mothers who have thalassemia children with support group therapy. Respondents in this study were eight mothers of thalassemia patients who were divided into control groups and experimental groups. The scale used in this study is the Modified Connor-Davidson Resilience Scale. This study used a quasi-experimental design with a pretest-posttest control group design with follow-up. Data obtained in the study were analyzed using the Mann-Whitney nonparametric test to compare scores between groups given Therapy Support Groups and groups not given intervention. The results showed that there were differences in resilience scores between the control group and the experimental group after being given Support Group Therapy, with p = 0.024 (p <0.05). This study concluded that support group therapy was effective for increasing resilience in mothers who had children with thalassemia.